Experiencing the Call of Duty: Exploring Emotions in Commercial War Games - Joseph Pattison (Media and Communication)
This article explores how players interpret and reflect on themes in mainstream war videogames, specifically the Call of Duty franchise. Scholars have long focused on the ideological content of war games, which is marked by increased collusion of military institutions with the gaming industry and assumptions about the influential capabilities of war games, in which player agency is often downplayed. This study builds on Lenoir and Caldwell’s (2018) observations that the interpretation of mainstream franchises should focus more on their attempts to create an “affective framework” that emphasises certain emotions in players. Through a thematic analysis of semi-structured interviews with 25 participants, this study found that participants outlined their discomfort in certain missions, to the point where they even altered their playstyle, suggesting that players often reflect critically on the aspects of war these games explore. This article concludes that mainstream franchises, like Call of Duty, should be considered complex cultural artefacts consisting of various layers of meaning. Rather than directly transmitting militaristic ideologies, these games craft an emotional aesthetic capable of exploring more controversial aspects of war. The key to understanding these franchises lies directly with the players themselves, which is why audiences should be treated as conscious agents who play an active role in drawing meaning from such an aesthetic.